2020
DOI: 10.1186/s10033-020-00465-z
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Passive Gait-based Ankle-foot Exoskeleton with Self-adaptive Capability

Abstract: Propulsion during push-off is the key to realizing human locomotion. Humans have evolved a way of walking with high energy utilization, but it can be further improved. Drawing inspiration from the muscle-tendon unit, a passive spring-actuated ankle-foot exoskeleton is designed to assist with human walking and to lengthen walking duration by mechanically enhancing walking efficiency. Detection of the gait events is realized using a smart clutch, which is designed to detect the contact states between the shoe so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The ankle joint supports the human body’s activities such as standing, walking, sitting, and standing transfer, the ankle joint provides most of the energy to support the individual’s activities. 30,31 The lightweight passive ankle exercise device studied by Wang et al 32 consists of four parts: the clever clutch, an extension spring, a shank brace, and a shoe, the spring can store and release energy, as shown in Figure 8. The device can assist the walking process, allow the ankle to move freely, which is suitable for nearly all users.…”
Section: Resultsmentioning
confidence: 99%
“…The ankle joint supports the human body’s activities such as standing, walking, sitting, and standing transfer, the ankle joint provides most of the energy to support the individual’s activities. 30,31 The lightweight passive ankle exercise device studied by Wang et al 32 consists of four parts: the clever clutch, an extension spring, a shank brace, and a shoe, the spring can store and release energy, as shown in Figure 8. The device can assist the walking process, allow the ankle to move freely, which is suitable for nearly all users.…”
Section: Resultsmentioning
confidence: 99%
“…Ankle exoskeletons can be classified as either passive or active. Passive ankle exoskeletons ( Collins et al, 2015 ; Wang et al, 2020 ) store energy in elastic structures during early parts of stance phase and release it during push-off. Since there are no power supplies and electronics, these devices are extremely lightweight, but their controllability is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In recent years, studies have shown that passive lower extremity exoskeletons that do not require external power that can also reduce the energy consumption of human walking, it uses the transformation of users' own energy to achieve the goal of improve mobility, 10,11 and many research related to the passive ankle exoskeleton are reported. 12,13 A passive exoskeleton was developed by Steven H. Collins et al in 2015, it is a lightweight spring device that parallels the spring with the user's calf muscles, thereby reducing muscle strength and reducing metabolic energy consumed by muscle contraction. The device uses a mechanical clutch to support the spring.…”
Section: Introductionmentioning
confidence: 99%